To Produce or to Survive: How Plastic Is Your Crop Stress Physiology? - Dalal, Ahan; Attia, Ziv; Moshelion, Menachem (Frontiers in Plant Science, 2017)
Abiotic stress causes major crop losses and is considered a greater challenge than biotic stress. Comparisons of the number of published articles and patents regarding these different types of stresses, and the number of commercially released crops designed to tolerate different types of stresses, revealed a huge gap in the bench-to-field transfer rate of abiotic stress-tolerant crops, as compared to crops designed to tolerate biotic stress. These differences underscore the complexity of abiotic stress-response mechanisms. Here, we suggest that breeding programs favoring yield-related quantitative physiological traits (QPTs; e.g., photosynthesis rate or stomatal conductance) have canalized those QPTs at their highest levels. This has affected the sensitivity of those QPTs to changing environmental conditions and those traits have become less plastic. We also suggest that breeding pressure has had an asymmetric impact on different QPTs, depending on their sensitivity to environmental conditions and their interactions with other QPTs. We demonstrate this asymmetric impact on the regulation of whole-plant water balance, showing how plastic membrane water content, stomatal conductance and leaf hydraulic conductance interact to canalize whole-organ water content. We suggest that a QPT’s plasticity is itself an important trait and that understanding this plasticity may help us to develop yield-optimized crops.